Regulation of eye and jaw colouration in three-spined stickleback Gasterosteus aculeatus - Franco-Belussi, L. [UNESP]; De Oliveira, C. [UNESP]; Sköld, H. N. (Wiley, 2018)
Fish can change their skin and eye colour for background matching and signalling. Males of Gasterosteus aculeatus develop ornamental blue eyes and a red jaw during the reproductive season, colours that are further enhanced during courtship. Here, the effects of different hormones on physiological colour changes in the eyes and jaws of male and female G. aculeatus were investigated in vitro. In an in vivo experiment, G. aculeatus were injected with a receptor blocker of a pivotal hormone (noradrenaline) that controls colour change. In males, noradrenaline had aggregating effects on melanophore and erythrophore pigments resulting in blue eyes and a pale jaw, whereas melanocyte-concentrating hormone (MCH) and melatonin resulted in a pale jaw only. When noradrenalin was combined with melanocyte stimulating hormone (MSH) or prolactin, the jaw became red, while the eyes remained blue. In vivo injection of yohimbine, an alpha-2 adrenoreceptor blocker, resulted in dispersion of melanophore pigment in the eyes and inhibited the blue colouration. Altogether, the data suggest that noradrenalin has a pivotal role in the short-term enhancement of the ornamental colouration of male G. aculeatus, potentially together with MSH or prolactin. This study also found a sex difference in the response to MCH, prolactin and melatonin, which may result from different appearance strategies in males, versus the more cryptic females.
Keywords: erythrophore; hormone; iris; melanophore; ornament; physiological colour change